Scaffolding dalam Menyelesaikan Masalah Matematika pada Materi Pertidaksamaan Linear Satu Variabel Kelas VII - Sri Handayani; Ika Kurniasari (Program Studi S1 Matematika UNESA, 2023)
The activity of finding solutions to math problems is not easy. Most of the seventh grade junior high school students had difficulties in solving problems related to one variable linear inequalities material. Students experience difficulties in solving problems at the Polya problem solving stage. The difficulties experienced by students can be helped by providing scaffolding. This study aims to describe the process carried out by students in solving mathematical problems in the material of one-variable linear inequalities, and to describe the provision of scaffolding in solving mathematical problems in the material of one-variable linear inequalities. This study uses the selection of subjects by administering tests. Thus, it can be seen clearly the stages of solving the questions carried out by students. The research was conducted at SMP Negeri 25 Surabaya, which was attended by 32 students of class VII. The PtLSV problems given are two questions. A total of three research subjects were taken from the initial test, of the three subjects who experienced difficulties at all stages of solving the Polya problem, they would be interviewed and given scaffolding. The results showed that students experienced difficulties in the process of solving mathematical problems in the material of one variable linear inequality. This can be seen from the results of the students' work which did not write down any information that was known and asked about the questions, students could not devise a solution plan for the questions given. Students do not carry out the completion plan, and students do not re-check the answers that have been obtained. Providing scaffolding in this study, adjusted the location of the difficulties experienced by students in solving problems. Keywords: Problem Solving, Scaffolding, One Variable Linear Inequality